Factors affecting the economic growth of Organization of Islamic Cooperation (OIC) member countries - Fauzan, Ahmad; Irfany, Mohammad iqbal (Halal Studies and Society, 2025)
Economic growth is widely used as a macroeconomic indicator for describing economic performance and, by extension, shifts in material living standards. Therefore, this study centers on the Organization of Islamic Cooperation (OIC), an international forum with predominantly Muslim member states, and examines the relationship between selected macroeconomic variables and economic growth across OIC countries from 2000 to 2021, a timeframe marked by two major global economic crises. In order to achieve the stated objective, panel data regression was applied to observations from 34 countries with complete data on inflation, net exports, gross fixed capital formation, real interest rates, working-age population, and total population. Panel regression was estimated under the Common Effects Model (CEM), Fixed Effects Model (FEM), and Random Effects Model (REM), with model selection based on specification tests. The Chow test (F = 167.4303; p = 0.0000) and Hausman test (² = 101.8431; p = 0.0000) consistently support the FEM as the preferred model. FEM results indicate that inflation and the real interest rate negatively and significantly affect GDP (INF: β = 0.007252, p = 0.0000; RIR: β = 0.008265, p = 0.0000), while net exports, gross fixed capital formation, working-age population, and population positively and significantly influence GDP (LnNetExp: β = 0.228393, p = 0.0000; LnGFC: β = 0.321654, p = 0.0000; PAK: β = 0.007255, p = 0.0104; LnPOP: β = 0.790510, p = 0.0000). All variables are jointly significant (F-statistic = 6735.187; p = 0.0000), and the model exhibits very high explanatory power (R² = 0.997722; adjusted R² = 0.997574). The findings underscore the critical role of price stability and real borrowing costs, alongside trade performance, capital accumulation, and demographic–labor dynamics, in shaping growth trajectories across OIC economies.